Wireless communications and networking for unmanned aerial vehicles - Saad, Walid ca. 20./21. Jh; Bennis, Mehdi ca. 20./21. Jh; Mozaffari, Mohammad 1989-; Lin, Xingqin 1987- (Cambridge University Press, 2020)
A thorough treatment of UAV wireless communications and networking research challenges and opportunities. Detailed, step-by-step development of carefully selected research problems that pertain to UAV network performance analysis and optimization, physical layer design, trajectory path planning, resource management, multiple access, cooperative communications, standardization, control, and security is provided. Featuring discussion of practical applications including drone delivery systems, public safety, IoT, virtual reality, and smart cities, this is an essential tool for researchers, students, and engineers interested in broadening their knowledge of the deployment and operation of communication systems that integrate or rely on unmanned aerial vehicles